Parliamentary versus presidential political system: options for Egypt post January 2011 - Hamdy, Ashraf (AUC Knowledge Fountain, 2011)
The debate on the merits of the parliamentary system of government versus the presidential system has been going on for many years now. Recently the topic attracted increased empirical attention with studies that looked at the impact of the system of government on different political, economic, and social aspects. This work adds to the literature a study that, using a global data set, empirically analyzes the effects of the choice of government system on income inequality, the level of political freedom, and the level of civil liberties in a society in general with an application to Egypt in particular. The empirical analysis revealed a strong relationship between parliamentarism as a political system and income equality, political rights and civil liberties in a society. The parliamentary system of government appears to be advantageous, compared to the presidential system, in its effect on the three main aspects under evaluation.